The Role of Osteoporosis Medications in Fracture Healing - Parry, Nicola (MD Conference Express, 2014)
This article discussez current understanding of the potential role for pharmacologic agents in bone healing, particularly those used for osteoporosis treatment, of which parathyroid hormone shows the most clinical promise.